Anti cytokine therapy in chronic inflammatory arthritis. (October 2016) - Thompson, Charlotte; Davies, Ruth; Choy, Ernest
Highlights: This is a review looking at anti cytokine therapy in Rheumatoid Arthritis (RA), Psoriatic Arthritis (PSA) and Ankylosing Spondylitis (AS). The review explores the similarities and differences in the clinical features, treatments and cytokines involved in the development and propagation of the disease. Particular attention is paid to TNFα inhibitors IL-1ra, IL-6 and JAK kinase Inhibitors, anti IL23 and IL-12. It includes new developments with anti-IL-17 and IL 27. Abstract: This is a review looking at anti cytokine therapy in Rheumatoid Arthritis (RA), Psoriatic Arthritis (PSA) and Ankylosing Spondylitis (AS). The review explores the similarities and differences in the clinical features, as well as treatments and cytokines involved in the development and propagation of the disease. Particular attention is paid to TNFα inhibitors IL-1ra, IL-6 and JAK kinase Inhibitors, anti IL23 and IL-12 and the new developments with anti-IL-17.